(untitled) (The Review of Diabetic Studies, 2024)
Background: The nursing workforce represents a critical component of the healthcare system in Saudi Arabia, which is facing significant challenges related to retention and job satisfaction. High turnover rates among nurses not only compromise patient care quality but also place additional strain on the healthcare system. Working in hospitals usually entails extraordinary psychological and emotional stress in which the nursing staffs have numerous relationships with others, particularly the nursing managers. The increase in work-related stressors and job strain can affect nurses’ job security. Key factors influencing these included income level, nationality, work-life balance, and opportunities for professional development. Notably, a significant inverse relationship was observed between job satisfaction and the intention to leave, highlighting the importance of addressing these factors to enhance retention. The aim of this literature review was to investigate the factors associated job security among nurses and leadership styles in health sector in Saudi Arabia 2024. Methods: A comprehensive literature review was conducted, examining peer-reviewed articles, official reports, and relevant studies up to December 2024. The review focused on empirical research that specifically addressed the factors influencing the associated job security among nurses and leadership styles in health sector in Saudi Arabia 2024. Results: This systematic review provides a detailed summary of the up-to-date studies on the Factors Associated between Leadership and Job Security among Nurses Working in health sector through 6 cross-sectional studies published between 2020 and 2024 , The results of this review showed significant differences between pay, years of experience, nationality, marital status, and nurses’ job satisfaction. Conclusion: This review reveals the complex interplay of factors influencing the associated job security among nurses and leadership styles in health sector in Saudi Arabia emphasizing the roles of job satisfaction, work environment, professional development, and demographic characteristics. It calls for targeted interventions to enhance job satisfaction and retention among nurses, highlighting the importance of a supportive work environment and opportunities for career advancement.